2003
DOI: 10.1038/sj.leu.2402940
|View full text |Cite
|
Sign up to set email alerts
|

In BCR-ABL-positive cells, STAT-5 tyrosine-phosphorylation integrates signals induced by imatinib mesylate and Ara-C

Abstract: In BCR-ABL-positive cells, the transcription factor STAT-5 is constitutively activated by tyrosine phosphorylation. activation results in upregulation of bcl-X L and increased resistance to induction of apoptosis. Here, we investigated the effects of imatinib mesylate and cytosine arabinoside (Ara-C) on STAT-5 tyrosine-phosphorylation, cellular proliferation and induction of apoptosis in cell lines and primary hematopoietic cells. Imatinib mesylate treatment strongly suppressed STAT-5 tyrosine-phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…The percentage of apoptotic cells was determined by measurement of the fraction with sub-G1 DNA content upon propidium iodide incorporation as described earlier (Kindler et al, 2003;Heidel et al, 2006). Briefly, 4 Â 10 4 cells were treated with various inhibitors for 24 or 48 h, collected and washed with PBS.…”
Section: Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of apoptotic cells was determined by measurement of the fraction with sub-G1 DNA content upon propidium iodide incorporation as described earlier (Kindler et al, 2003;Heidel et al, 2006). Briefly, 4 Â 10 4 cells were treated with various inhibitors for 24 or 48 h, collected and washed with PBS.…”
Section: Antibodiesmentioning
confidence: 99%
“…MNCs were isolated by Ficoll density-gradient centrifugation as described earlier (Kindler et al, 2003). For purification of CD34 þ cells, fresh leukapheresis, peripheral blood or bone marrow samples from CML patients or healthy donor were collected.…”
Section: Antibodiesmentioning
confidence: 99%
“…Preparation of cellular lysates was performed as described. 48 Supernatants were shock frozen and stored at Ϫ80°C. Protein concentration was measured by using the Bradford assay.…”
Section: Protein Extract Preparationmentioning
confidence: 99%
“…It competitively binds to the ATP-binding site of BCR.ABL and inhibits protein tyrosine phosphorylation in vitro and in vivo [66]. In vitro studies had shown that Imatinib is capable to inhibit cell proliferation of cell lines expressing Bcr-Abl [67][68][69], effect accomplished through JAK5-STAT and PI3 kinase signaling inhibition [70,71]. It has also been shown that STI571 can inhibit CML MNC, obtained both in chronic phase and blast crisis [71] and reduces the colony forming cells from Mobilized Peripheral Blood (MPB) and Bone Marrow from patients with CML in chronic phase [60].…”
Section: Imatinibmentioning
confidence: 99%